Painful and Prolonged Muscle Cramps following Insulin Injections in a Patient with Type 2 Diabetes Mellitus: Revisiting the 1992 Duke Case - Ballout, Rami A.; Arabi, Asma (Frontiers in Endocrinology, 2017)
A 56 year-old middle-eastern male with a long-standing history of poorly-controlled type 2 Diabetes Mellitus presented to us complaining of severely painful bilateral upper and lower extremity cramps occurring shortly after his rapid-acting insulin analogue injection(s). The cramps had started 6 months ago and have been occurring intermittently in non-predictable episodes since then. He had otherwise never experienced any insulin-related adverse reaction(s) before. His cramps are very painful and debilitating, interfering with his daily activities and placing him in a state of constant fear/anxiety of re-experiencing them. This caused him to become non-adherent with his prescribed treatment, and poorly compliant with his follow-up regimens. Thorough examination showed a diffuse loss of sensation over the lower limbs. This was subsequently confirmed with a combined electromyography-nerve conduction study which indicated extensive diabetic axonal polyneuropathy. In contrast, lower extremity segmental arterial pressures were negative for peripheral vasculo-occlusive disease, ruling out vascular insufficiency as a possible etiology of the cramps. We then measured the levels of serum electrolytes right-before and 30 minutes right-after injecting the patient with his insulin. Potassium dropped by about 16 % from its initial level, compared to a drop of only around 4% for calcium and none (0%) for magnesium. Thus, we speculated this insulin-induced sharp drop in serum potassium levels as potentiating the patient’s already existing advanced diabetic neuropathy, thereby leading to muscle cramping. However, attempting potassium supplementation for a brief period of time led to a rapid resolution of cramps when they occurred, and an overall reduction in their frequency of recurrence. This tilted our diagnosis towards the insulin-induced acute drop in serum potassium levels as the most likely etiology underlying the patient’s cramps. Such an observation has been made only once previously within the literature, back in 1992, at the Duke University Medical Center.